Study of Floating Condensing for Energy saving on refrigeration plants in tropical areas - Guidi, Clotilde; SEMASSOU, GUY CLARENCE (My University, 2016)
The present research work concerns the energy saving on refrigeration plants in warm tropical areas. The object is to optimize the operating cost of the cold stores for food industries by computing the energy consumption of the refrigeration systems for various changes of the outside temperature. The energy needs for compressors diminish as the compression rate becomes low for colder outside temperatures. The determined fans energy consumption shows a very slight increase when outdoor temperature increases, thus this can be considered as almost constant. The floating HP operating mode shows obviously a better COP than the fixed HP one. Performing the calculation algorithm with several refrigerants, i.e. R717, R404A and R22 the results show that the COP is better for ammonia, then follow the performances of R22 and R404A. The annual energy gain is at least 600kWh/ kW of cooling capacity compared to the fixed HP operating mode. Considering the energy consumption, the refrigerant R404A presents the best gain (17%), and 13% for ammonia. Although temperature does not change a lot over the year in the humid tropical areas concerned, 15% energy saving can be predicted with floating condensation pressure control. For industrial refrigerating plant, the method appears very promising for energy saving. Involving a very small investment, it allows a good competitiveness. It can also permit the design and the management of more environmentally sustainable industrial refrigeration plants.
Keywords: Energy saving; floating condensing; environment; refrigeration